Performance of Indonesian Batik SMEs: An analysis of Green Intrinsic Motivation, Green communication, and Green Compensation - Ria Emerensiana; Saputra Asep Rokhyadi Permana; Rispantyo (Journal of Engineering Management and Competitiveness)
Globalization demands the importance of environmental awareness and sustainability to achieve competitive advantage, including Batik Jogyakarta SMEs in Indonesia which are required to implement environmentally friendly business practices. This study aims to analyse the effect of green intrinsic motivation, green communication, and green compensation on employee performance. To answer the research objectives, the sampling method is random sampling, with quota sampling techniques, and data collection with Google Forms. The model used is the Structural Equation Modelling (SEM). To test the hypothesis, using an analysis tool with the rho test, validity test with the Convergent Validity test and loading factor, discriminant validate test with Fornell-Larcker Criteria, reliability test with Cronbach Alpha, Composite Reliability and AVE, and all using SmartPLS software version 4. From a sample of 158 respondents, the results are that Green Intrinsic Motivation and Green Communication have a positive and significant effect on Green Employee Performance. However, Green Compensation is not proven. The practical implications of these findings are the importance of strengthening sustainability strategies by integrating challenging environmental activities into daily work, improving communication, and developing innovative reward systems to create a more environmentally friendly work culture and empower employees to contribute to sustainability.